2019
DOI: 10.1108/rege-01-2018-0014
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the spirit of initiative and identification with the organization on IT governance effectiveness perception in public organizations

Abstract: Purpose -The purpose of this paper is to address the process of organizational governance of IT resources, called IT governance (ITG), especially its behavioral approach. The organizational citizenship behavior (OCB) concept was used to understand the relationship between the behavioral dimensions and the perception of ITG effectiveness. The objective of this research is to identify if individuals' behavior contributes to a greater perception of ITG effectiveness in public organizations. This is an exploratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
(64 reference statements)
0
2
0
1
Order By: Relevance
“…From a cultural-cognitive perspective, the legitimacy of the ITG Structure arises from an individual's perception of its effectiveness, which creates a reference structure from which other organizations may learn and copy [7,41]. Additionally, from a regulatory perspective, an organization's compliance with rules and regulations serves as evidence of the implementation of ITG mechanisms [26].…”
Section: -1-it Governancementioning
confidence: 99%
See 1 more Smart Citation
“…From a cultural-cognitive perspective, the legitimacy of the ITG Structure arises from an individual's perception of its effectiveness, which creates a reference structure from which other organizations may learn and copy [7,41]. Additionally, from a regulatory perspective, an organization's compliance with rules and regulations serves as evidence of the implementation of ITG mechanisms [26].…”
Section: -1-it Governancementioning
confidence: 99%
“…Clarity regarding roles and responsibilities reduces ambiguity and conflicts in individuals' perceptions of their assignments and organizational roles [67]. By defining key roles and responsibilities in the deployment of ITG mechanisms, organizations contribute to supporting individuals involved in ITG, facilitating their understanding of their roles, ensuring the integrity and responsible behaviors required by ITG processes, enhancing the perception of organizational support, and enabling employees to handle work displeasures without complaining [7,68]. This argument leads us to the following hypothesis: H1c: ITG institutionalization positively affects sportsmanship.…”
Section: Figure 2 Research Modelmentioning
confidence: 99%
“…Tata Kelola IT pada pemerintahan dapat dipahami sebagai aspek finansial dan administrasi untuk mengimplementasikan kebijakan publik. Tata Kelola TI bukan diperuntukkan untuk departemen TI saja, melainkan bagaimana adopsi TI dan kegunaannya bagi organisasi [62].…”
Section: Tata Kelolaunclassified
“…Other three papers, after a set of studies in the Brazilian government subnational level, claim that ITG institutionalization exerts a positive effect on behavior since the ITG legitimation process enhances the perception of organizational justice through transparency and equity increase (Wiedenhöft, Luciano, & Macadar, 2016;Wiedenhöft, Luciano, & Pereira, 2019;Wiedenhöft, Luciano, & Porto, 2019). A more recent research showed that when OCB levels are higher, ITG is more easily perceived as effective (Wiedenhöft, Luciano, & Pereira, 2019).…”
Section: It Governance Behavioral Approachrelated Workmentioning
confidence: 99%
“…Therefore, the ITG mechanisms' adoption level can be influenced by a cognitive institutionalization process resultant from a regulatory, normative, or mimetic pressure related to the perceived importance of the ITG mechanisms (Scott, 1995). Consequently, the IT governance mechanisms maturity (ITGMM) can vary depending on the individual behavior, and it is measured by the mechanisms' adoption level and its contribution to reaching the goals while principles are respected (Currie, 2008;Wiedenhöft, Luciano, & Porto, 2019). ITG principles work also as a promoter of strategic alignment (Luna-Reyes, Juiz, Gutierrez-Martinez, Duhamel, 2020).…”
Section: Introduction Introductionmentioning
confidence: 99%